2014
DOI: 10.15376/biores.9.3.5024-5033
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis for Fiber Characteristics and Strength Properties of Softwood Kraft Pulps from Different Stages of a Bleaching Fiber Line

Abstract: During sequential bleaching operations, pulp fiber properties are gradually changed due to mechanical and chemical treatments. In this study, the correlations between pulp or fiber properties such as kappa number, viscosity, total charge, fiber length, and zero-span tensile strength as well as Scott bond of elemental chlorine free (ECF) bleached softwood kraft pulps was investigated. The influence of zero-span tensile strength and Scott bond on tensile and tear strength was also discussed. The Scott bond and z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…These relationships were highly significant and explained more than 81% of the total variation in tear index (Figure 4a). This close relationship between the zero-span breaking length and tear index is in good agreement with previous findings [5][6][7][8]51]. The difference between hardwood and softwood pulps is due to the impact of fibre length on the development of tear index.…”
Section: Impact Of Fibre Strength On the Development Of Paper Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…These relationships were highly significant and explained more than 81% of the total variation in tear index (Figure 4a). This close relationship between the zero-span breaking length and tear index is in good agreement with previous findings [5][6][7][8]51]. The difference between hardwood and softwood pulps is due to the impact of fibre length on the development of tear index.…”
Section: Impact Of Fibre Strength On the Development Of Paper Propertiessupporting
confidence: 92%
“…Several studies [5,26,41,[44][45][46][47][48][49][50][51] demonstrated that during rupture in tensile testing of paper, some fibres pull out and others break. Beating weakens the fibres and the proportion of broken fibres during paper testing increases with the beating level.…”
Section: Impact Of Fibre Strength On the Development Of Paper Propertiesmentioning
confidence: 99%
“…In wood, fibers are mostly straight and it is known that fibers can become curlier in the unit processes along the fiber line, as the fibers are subjected to mechanical forces in for example pumps, pipes and screw presses (Courchene et al 2002;Joutsimo and Giacomozzi 2015;Koskinen et al 2009;Lin et al 2014;Page et al 1985). However, in the present study the pulps were oxygen delignified in autoclaves, with alkali, oxygen and only mixing by gentle kneading and shaking of the pulp, yet oxygen delignified pulps had much higher curl and kinks than kraft cooked pulps.…”
Section: Effect On Morphologymentioning
confidence: 99%
“…In general, the bonding area among fibers increases with fiber length and decreases with cell wall thickness. Since the interfiber bonding area is related to the burst and tensile strengths of paper, the fiber length and cell wall thickness play an important role in governing paper mechanical properties 33‐37 . Accordingly, long and thin fibers become a paper of high density, low stiffness, low ink adsorption and smooth surface which is suitable for printing paper.…”
Section: Introductionmentioning
confidence: 99%